Operational and energy performance of the tractor-scarifier assembly: Tires, ballasting and soil cover - José E. L. Lopes; Carlos A. Chioderoli; Leonardo de A. Monteiro; Mara A. M. dos Santos; Eric H. C. B. van Cleef; Elivânia M. S. Nascimento (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The heights of tire claws, tractor ballasting and soil cover can influence the operational and energy performance of the tractor-scarifier assembly. The objective of this study was to analyze the operational and energy performance of the tractor-scarifier assembly as a function of the heights of the tire claws, ballasting and rolling surface. The experiment was conducted at the experimental area of the Fazenda Experimental do Vale do Curu of the Universidade Federal do Ceará in Pentecoste municipality, CE, Brazil. The experiment was carried out in a randomized block in a 2 × 2 × 2 factorial arrangement with four repetitions. The treatments comprised two tire claw heights (T1-28% and T2-100%), two ballasts (B1-100% of solid and 75% liquid weights and B2 - 0% of solid and liquid weights), and two soil surfaces (S1 - soil with 4200 kg of straw ha-1 and S2 - mobilized soil). Worn tires provided a lower bar force (12.88 kN) and power requirement (20.06 kW) and a greater effective and operative field capacity of the tractor-scarifier assembly. The lowest slippage of the front wheels of the tractor was recorded for the worn tires (4.81%).For the rear wheels, slippages were found on the new tires (10.96%), and a higher speed of displacement was found for worn tires (5.54 km h-1). Lower specific fuel consumption was found for the mobilized soil (534.68 g kWh-1); furthermore, the hourly consumption of fuel and the consumption per area were not significantly affected by the treatments analyzed.